How Long is the Safest InterDelivery Interval in Women with Previous History of Cesarean Delivery? - Budi I Santoso; Raymond Surya; Karina K Firdaus; Surahman Hakim (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between interdelivery interval and uterine rupture in women with previous CD. Methods: The formulation question was how long is the safest interdeliveryinterval to minimalize the risk of uterine rupture. Theauthors investigated in three databases including Pubmed,Cochrane, and Embase database. Inclusion criteria wereabstract answering the clinical question, written in Englishlanguage, and full-text paper availability. Results: One systematic review, six cohort studies, and 1 casecontrolstudy were collected to compare the inter-pregnancyinterval to the risk of uterine rupture. The author retrievedseven articles suitable to the inclusion criteria after excluding tenarticles screened by the abstract and language. Then, the authoradded one article used in the systematic review. Hence, the criticalappraisal based on Validity, Importance, and Applicability (VIA)was performed for eight articles. Conclusion: The inter-delivery interval ï‚³18 months is the safest time to avoid uterine rupture. Prostaglandin analogue induction should be avoided and for patients with a history of past cesarean using a single-layer closure to be educated about the increased risk. Keywords: cesarean delivery, inter-delivery interval, uterine rupture,vaginal birth after cesarean delivery